Variant PCGF1-PRC1 links PRC2 recruitment with differentiation-associated transcriptional inactivation at target genes - Hiroki Sugishita (Nature Portfolio, 2021)
Polycomb repressive complexes (PRC1 and PRC2) repress genes that are crucial for development via epigenetic modifications; however, their role in differentiation is not well known. Here the authors reveal that a PCGF1-containing PRC1 variant facilitates exit from pluripotency by downregulating target genes and recruiting PRC2.